Trends in infections detected in women with cervicitis over a decade - Vodstrcil, Lenka A.; Plummer, Erica L.; Nguyen, Thuy Vy; Fairley, Christopher K.; Chow, Eric P. F.; Phillips, Tiffany R.; Bradshaw, Catriona S. (Frontiers in Reproductive Health, 2025)
ObjectivesThere is a growing body of evidence that in the absence of Chlamydia trachomatis and/or Neisseria gonorrhoeae, Mycoplasma genitalium and bacterial vaginosis (BV) are associated with cervicitis. We aimed to describe infections detected among cervicitis cases over a decade and establish how commonly M. genitalium and BV were detected among non-chlamydial/non-gonococcal cases to inform testing and treatment practices.MethodsWe conducted a retrospective case-series to determine the number of cervicitis cases diagnosed with genital infections (C. trachomatis, N. gonorrhoeae, M. genitalium and BV) among women attending the largest public sexual health service in Australia from 2011 to 2021. We determined the proportion of cervicitis cases with one or more genital infections detected, and trends in testing and detection of each infection over time.ResultsOver a decade 813 cervicitis cases were diagnosed; 421 (52%, 95%CI: 48%–55%) had no infection detected; 226/729 (31%, 95%CI: 28%–35%) had BV, 163/809 (20%, 95%CI: 17%–23%) C. trachomatis, 48/747 (6%, 95%CI: 5%–8%) M. genitalium, and 13/793 (2%, 95%CI: 1%–3%) N. gonorrhoeae. Of the 665 (82%) cases tested for all four infections, 268 (40%) had one infection and 73 (11%) had >1 infection detected. Of the 517/665 (78%) non-chlamydial/non-gonococcal cases, 164 (32%) had BV and 16 (3%) had M. genitalium as the sole infections detected; a further 13 cases (3%) were co-infected with BV and M. genitalium. The proportion of cases tested for BV (90%) did not change overtime, but detection increased from 32% to 45% (Ptrend < 0.001). The proportion of cases tested for M. genitalium increased from 84% in 2011 to 96% in 2019 (Ptrend = 0.006), with M. genitalium-detection in cervicitis increasing from 3% to 7% (Ptrend = 0.046).ConclusionsIn our study population, chlamydia or gonorrhoea were not detected in ∼75% of cervicitis cases; 1 in 3 of these cases had BV and/or M. genitalium, and both increased in prevalence over time. These data highlight the need for clinicians to consider BV and M. genitalium when assessing and managing cervicitis.